Report of the Expert Group on Estimation of Proportion and Number of Poor - Planning Commission (Planning Commission, 1993)
A number of methodological issues have been raised in respect of the estimates of poverty released by the Planning Commission. In view of the importance of poverty eradication as a social objective, wide ranging references to the incidence of poverty in discussions relating to social problems as also their use in allocation of funds for poverty alleviation programmes, it was thought that all the issues relating to the estimation of poverty could be considered afresh by an expert group. The Planning Commission constituted, in September 1989, an 'Expert Group' to consider methodological and computational aspects of estimation of proportion and number of poor in India. The terms of reference of the Expert Group are as follows.
Perspective Planning Division Planning Commission Government of India